Corrosion-resistant magnet and magnetic attractor
Patent Information
- Application Number
- JP2023132057
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-14
- Publication Date
- 2025-02-27
- Estimated Expiration
- 2043-08-14
AI Technical Summary
【0015】 上記各態様によれば、高湿度環境あるいは水中での長期使用にも耐えられるより高い耐腐食性を備えた耐腐食磁石、及び、この耐腐食磁石を備えた磁気吸着装置を提供できる。
Smart Images

Figure 2025027332000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a corrosion-resistant magnet and a magnetic attraction device. [Background technology]
[0002] Currently used permanent magnets, such as neodymium, samarium-cobalt, alnico, and ferrite magnets, are primarily designed for use in the atmosphere, and have never been designed for use in high humidity environments or seawater. In particular, neodymium magnets cannot be used unless their surface is nickel-plated because the main material, neodymium (Ne), is a base metal with an electrode potential of around -2,400 mV (SCE). If moisture or water gets into the magnet when it is used in the air, it will form a galvanic battery with other metal materials and become the anode, which will dissolve and disintegrate. As such, permanent magnets are designed to be used in the atmosphere, and their use in seawater was not considered. Furthermore, even when neodymium magnets first appeared, no corrosion prevention measures were taken other than nickel plating on the surface.
[0003] The inventors planned to use the adhesive force of a neodymium magnet instead of underwater welding as a means of attaching an Al anode for cathodic protection in seawater. In order to increase the adhesive force of the neodymium magnet and prevent corrosion in seawater, they developed a "magnetic adhesive device" in which the neodymium magnet is housed in a yoke, and then further filled with flexible zinc anode material, and a sacrificial anode layer is formed to provide cathodic protection functionality (see Patent Document 1 below). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 5090781 Summary of the Invention [Problem to be solved by the invention]
[0005] The magnetic attraction device is highly regarded as an alternative technology to conventional fastening methods such as welding, due to its high attraction performance and ease of use. It is hoped that the range of applications will be further expanded by taking advantage of its convenience, but considering its long-term use in humid and wet environments, the magnets used in the device must have even greater corrosion resistance. For example, neodymium magnets are suitable as magnets, but neodymium magnets are made by sintering materials such as neodymium (Ne), boron (B), and ferrite (Fe), and their surface is porous, making them susceptible to moisture and water penetration. When moisture and water penetration occurs, a dissimilar metal contact battery (galvanic battery) is formed between the materials, and the neodymium-rich part, which has a lower potential, becomes the anode and dissolves. Therefore, as a measure to prevent moisture and water penetration, neodymium magnets are used with their surface covered with a nickel plating layer. However, the nickel plating layer itself is porous and has many pores on its surface, so further improvements are required for long-term use in high humidity environments and underwater.
[0006] The present invention has been made in consideration of the above circumstances, and has an object to provide a corrosion-resistant magnet having high corrosion resistance capable of withstanding long-term use in a high humidity environment or underwater, and a magnetic attraction device equipped with this corrosion-resistant magnet. [Means for solving the problem]
[0007] In order to solve the above problems and achieve the above object, the present invention employs the following aspects. (1) A corrosion-resistant magnet according to one embodiment of the present invention is A permanent magnet coated with nickel; a zinc coating formed on the nickel coating; has. (2) In the corrosion-resistant magnet described in (1) above, the zinc coating may be zinc plating. (3) In the corrosion-resistant magnet described in (1) above, the zinc coating may be a zinc tape.
[0008] According to the corrosion-resistant magnets described in (1) to (3) above, the pores on the surface of the nickel coating are covered with the zinc coating. Therefore, even if this corrosion-resistant magnet is used for a long period of time in a high humidity environment or underwater (including seawater), moisture or water will not reach the permanent magnet through the pores in the nickel coating, so dissolution of the permanent magnet can be prevented. Therefore, this corrosion-resistant magnet has high corrosion resistance that can withstand long-term use in a high humidity environment or underwater.
[0009] (4) A corrosion-resistant magnet according to another aspect of the present invention is A permanent magnet coated with nickel; a first insulating layer made of an epoxy resin formed on the nickel coating; has. According to the corrosion-resistant magnet described in (4) above, the pores on the surface of the nickel coating are covered with the first insulating layer. Therefore, even if this corrosion-resistant magnet is used for a long period of time in a high humidity environment or underwater, moisture or water will not reach the permanent magnet through the pores in the nickel coating, and the permanent magnet can be prevented from dissolving. Therefore, this corrosion-resistant magnet has high corrosion resistance that can withstand long-term use in a high humidity environment or underwater.
[0010] (5) A magnetic adsorption device according to one aspect of the present invention, A corrosion-resistant magnet according to any one of the above (1) to (4), a yoke that holds the corrosion-resistant magnet; Equipped with. According to the magnetic attraction device described in (5) above, the corrosion-resistant magnet has high corrosion resistance that can withstand long-term use in a high humidity environment or underwater. Therefore, this magnetic attraction device can be used for a long period of time in a high humidity environment or seawater.
[0011] (6) The magnetic adsorption device according to (5) above, A zinc anode layer coating the corrosion resistant magnet The device may further include: According to the magnetic attraction device described in (6) above, the surface of the corrosion-resistant magnet is further covered with a zinc anode layer, so that it has higher corrosion resistance and can exhibit high magnetic attraction performance for a long period of time.
[0012] (7) The magnetic adsorption device according to (6) above may have the following configuration: The corrosion-resistant magnet is ring-shaped; The yoke is A back yoke portion that is attracted to the corrosion-resistant magnet; an outer yoke portion formed integrally with the back yoke portion and surrounding the corrosion-resistant magnet; an inner yoke portion disposed on the inner periphery side of the corrosion-resistant magnet and integrally formed with the back yoke portion; The zinc anode layer is Between an outer peripheral surface of the corrosion-resistant magnet and an inner peripheral surface of the outer peripheral yoke portion, Between an inner peripheral surface of the corrosion-resistant magnet and an outer peripheral surface of the inner peripheral yoke portion, a surface of the corrosion-resistant magnet opposite to an attracting surface with the back yoke portion; is formed. According to the magnetic attraction device described in (7) above, the surface of the corrosion-resistant magnet is further covered with a zinc anode layer, so that it has higher corrosion resistance and can exhibit high magnetic attraction performance for a long period of time.
[0013] (8) In the magnetic adsorption device according to (5) above, A second insulating layer made of epoxy resin formed on the surface of the corrosion-resistant magnet. The device may further include: According to the magnetic attraction device described in (8) above, the surface of the corrosion-resistant magnet is further covered with epoxy resin, so that it has higher corrosion resistance and can exhibit high magnetic attraction performance for a long period of time.
[0014] (9) The magnetic adsorption device according to (8) above may have the following configuration: The corrosion-resistant magnet is ring-shaped; The yoke is A back yoke portion that is attracted to the corrosion-resistant magnet; an outer yoke portion formed integrally with the back yoke portion and surrounding the corrosion-resistant magnet; an inner yoke portion disposed on the inner periphery side of the corrosion-resistant magnet and integrally formed with the back yoke portion; The second insulating layer is Between an outer peripheral surface of the corrosion-resistant magnet and an inner peripheral surface of the outer peripheral yoke portion, Between an inner peripheral surface of the corrosion-resistant magnet and an outer peripheral surface of the inner peripheral yoke portion, a surface of the corrosion-resistant magnet opposite to an attracting surface with the back yoke portion; is formed. According to the magnetic attraction device described in (9) above, the surface of the corrosion-resistant magnet is further covered with the second insulating layer, so that it has higher corrosion resistance and can exhibit high magnetic attraction performance for a long period of time. Effect of the Invention
[0015] According to each of the above aspects, it is possible to provide a corrosion-resistant magnet having high corrosion resistance capable of withstanding long-term use in a high humidity environment or underwater, and a magnetic attraction device including this corrosion-resistant magnet. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a longitudinal sectional view of a magnetic attraction device taken along a cross section including a central axis thereof, showing an embodiment of the present invention. [Diagram 2] FIG. [Diagram 3] 2 is a diagram for explaining the detailed structure of a corrosion-resistant magnet provided in the magnetic attraction device, and is an enlarged view of part A in FIG. [Figure 4] FIG. 4 is an enlarged cross-sectional view of part B in FIG. 3 turned upside down, showing the form coated with an electrolytic zinc plating layer. [Diagram 5] FIG. 5 is a partially enlarged cross-sectional view corresponding to FIG. 4, showing a form in which high-purity zinc tape is used instead of the electrolytic zinc plating layer. [Figure 6]FIG. 5 is a partially enlarged cross-sectional view corresponding to FIG. 4, showing a configuration in which a solvent-free epoxy resin coating is applied and covered in place of the electrolytic zinc plating layer. [Figure 7] FIG. 6 is a diagram showing a method for manufacturing the corrosion-resistant magnet shown in FIG. 5, with steps proceeding in the order of (a), (b), and (c). [Figure 8] FIG. 2 is a vertical cross-sectional view showing the main part of the magnetic attraction device shown in FIG. 1 turned upside down, showing a case where an insulating layer is formed by a solventless epoxy resin paint. [Figure 9] FIG. 9 is a vertical cross-sectional view corresponding to FIG. 8, showing a case where a sacrificial anode layer is formed by filling the periphery of a corrosion-resistant magnet with flexible zinc anodes. [Figure 10] This figure corresponds to Figure 8, and is a vertical cross-sectional view showing a corrosion-resistant magnet in which a neodymium magnet is covered with high-purity zinc tape and an insulating layer is formed by applying a solvent-free epoxy resin paint to the magnet. [Figure 11] This is a vertical cross-sectional view corresponding to Figure 8, showing a corrosion-resistant magnet in which a neodymium magnet is covered with high-purity zinc tape and a flexible zinc anode is filled around the magnet to form an insulating layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS An embodiment and various modified examples of a corrosion-resistant magnet and a magnetic attraction device including the same according to the present invention will be described below with reference to the drawings.
[0018] [Magnetic adsorption device] Fig. 1 is a diagram showing one embodiment of the present invention, and is a vertical sectional view of a magnetic attraction device 180 taken along a cross section including its central axis. Fig. 2 is an exploded perspective view of the magnetic attraction device 180. The magnetic attraction device 180 of this embodiment is particularly characterized by the corrosion-resistant magnetic attraction structure 176 including the corrosion-resistant magnet 110. In the following explanation, first, the overall configuration of the magnetic attraction device 180 will be explained based on Figures 1 and 2, and then the corrosion-resistant magnet 110 and the corrosion-resistant magnetic attraction structure 176 will be explained in detail.
[0019] 2, the magnetic attraction device 180 according to this embodiment includes an attraction device main body 180a and a nut 180b for fixing the attraction device main body 180a to equipment or the like. The bolt 188 is used by being screwed into the attraction device main body 180a, and is an attraction force adjustment member for adjusting the attraction force with respect to the attraction target by moving the magnetic attraction device 180 toward and away from the attraction target.
[0020] As shown in Fig. 2, the attraction device main body 180a includes a corrosion-resistant magnetic attraction structure 176 including the corrosion-resistant magnet 110, and a cap-shaped yoke 181 that houses the corrosion-resistant magnetic attraction structure 176. For the sake of explanation, Fig. 2 only illustrates the corrosion-resistant magnet 110, which is ring-shaped in plan view, of the corrosion-resistant magnetic attraction structure 176. A screw shaft portion 186 is formed on the surface of the yoke 181 opposite to the side facing the corrosion-resistant magnet 110.
[0021] 1, corrosion-resistant members 142a and 142b are provided in the gap between the yoke 181 and the corrosion-resistant magnet 110. Furthermore, a corrosion-resistant member 142c is provided on the lower surface of the corrosion-resistant magnet 110, i.e., the surface that is exposed to the outside when housed in the yoke 181. In this embodiment, the corrosion-resistant magnet 110 and the corrosion-resistant members 142a, 142b, 142c, and 142d (described later) that cover the corrosion-resistant magnet 110 constitute a corrosion-resistant magnetic attraction structure 176. Details of this corrosion-resistant magnetic attraction structure 176 will be described later.
[0022] The yoke 181 is configured by integrally forming a disk-shaped back yoke portion 183 that is attracted to the magnetic surface on the back side of the corrosion-resistant magnet 110, a cylindrical outer peripheral yoke portion 184 having an inner peripheral surface facing the outer peripheral surface of the corrosion-resistant magnet 110, an inner peripheral yoke portion 185 having an outer peripheral surface facing the inner peripheral surface of the corrosion-resistant magnet 110, and a screw shaft portion 186 provided on the side of the back yoke portion 183 opposite to the surface that is attracted to the corrosion-resistant magnet 110. The yoke 181 accommodates the corrosion-resistant magnetic attraction structure 176 in a groove portion 181b that is ring-shaped when viewed from the bottom and is formed by the back yoke portion 183, the outer peripheral yoke portion 184, and the inner peripheral yoke portion 185.
[0023] As described above, the magnetic attraction device 180 of this embodiment is able to obtain a strong attraction force by providing the inner yoke portion 185 and the outer yoke portion 184 that face the inner and outer periphery, respectively, of the ring-shaped corrosion-resistant magnet 110. In other words, by adopting such a double yoke structure, an attraction portion is formed between the corrosion-resistant magnet 110 and the inner yoke portion 185, and between the corrosion-resistant magnet 110 and the outer yoke portion 184, respectively, and the magnetic force of the corrosion-resistant magnet 110 can be efficiently used for attraction. Specifically, magnetic attraction device 180 with the double yoke structure described above can obtain an attractive force that is approximately 1.7 times higher than that of a magnetic attraction device with a configuration (single yoke structure) that does not include inner circumferential yoke portion 185. In this embodiment, by adopting the double yoke structure in this manner, the attractive force is greatly improved without increasing the dimensions, and even heavy equipment can be fixed with small magnetic attraction device 180.
[0024] In addition, as shown in FIG. 1, groove portion 181b of yoke 181 is formed to a depth greater than the height of corrosion-resistant magnetic attraction structure 176, and when corrosion-resistant magnetic attraction structure 176 is housed in yoke 181, the attraction surfaces on the opening sides of outer peripheral yoke portion 184 and inner peripheral yoke portion 185 protrude toward the tip side (toward object to be attracted 1000) beyond the surface of corrosion-resistant magnetic attraction structure 176. By having the yoke 181 protrude beyond the corrosion-resistant magnetic adhesion structure 176 in this manner, the corrosion-resistant magnetic adhesion structure 176 can be protected from friction and impact when the magnetic adhesion device 180 is attached to the object to be attracted 1000, and the corrosion-resistant magnetic adhesion structure 176 can be prevented from wearing out or cracking.
[0025] As shown in FIG. 2, the screw shaft portion 186 is formed in a cylindrical shape integral with the yoke 181, and the extension direction of the screw shaft portion 186 coincides with the normal direction of the outer surface of the back yoke portion 183. A male thread portion 186a is formed on the outer circumferential surface of the screw shaft portion 186 to which the nut 180b is screwed. The screw shaft portion 186, together with the nut 180b, functions as a member for attaching the magnetic adsorption device 180 to equipment or the like (not shown). That is, the screw shaft portion 186 can be easily attached to the equipment or the like by inserting it into a bolt hole H of a support bracket (reference symbol S in FIG. 1) provided on the equipment and then fastening the nut 180b. Note that the support bracket S in FIG. 1 extends toward the back side of the paper and is fixed to the equipment. Therefore, the equipment is fixed to the attraction target 1000 by the magnetic adsorption device 180 fixed to the support bracket S with the nut 180b being magnetically attracted to the attraction target 1000.
[0026] A threaded hole 181a is formed in the threaded shaft portion 186, penetrating the threaded shaft portion 186 in the axial direction. As shown in Fig. 1, the threaded hole 181a coaxially penetrates the back yoke portion 183 and the inner peripheral yoke portion 185 of the yoke 181. That is, the threaded hole 181a is formed penetrating the suction device main body 180a in the height direction.
[0027] A female thread is formed on the inner surface of the screw hole 181a to screw into the male thread 189 of the bolt 188. Because the screw hole 181a penetrates the suction device main body 180a, by screwing a bolt 188 of sufficient length into the screw hole 181a, the tip of the bolt 188 can be protruded from the tip of the inner yoke part 185. In addition, by rotating the bolt 188 forward or backward about its axis, the protruding length of the bolt 188 from the suction surface of the yoke 181 can be freely adjusted.
[0028] The nut 180b screwed onto the male threaded portion 186a of the screw shaft portion 186 is a locking nut, and in this embodiment, as shown in FIG. 2, a friction ring 187 is provided coaxially with the screw hole of the nut 180b. The friction ring 187 has a claw portion protruding toward the center of the screw hole, and when the nut 180b is screwed onto the screw shaft portion 186, the claw portion comes into contact with the thread of the male threaded portion 186a and deforms, and the reaction force generated by this deformation presses the male threaded portion 186a. The friction force generated between the friction ring 187 and the male threaded portion 186a restricts the free rotation of the nut 180b, preventing the nut 180b from loosening. The anti-loosening structure of the nut 180b is not particularly limited, and in addition to using a friction ring, various structures can be used, such as a structure using a spring washer, a double nut structure, and a structure using a resin ring.
[0029] 2, the back yoke portion 183 is formed with a plurality of screw holes (through holes) 183a that penetrate the back yoke portion 183 and reach the corrosion-resistant magnet 110. These screw holes 183a are used when the corrosion-resistant magnet 110 is accommodated in the yoke 181, and a bolt (not shown) is inserted into the screw hole 183a with the tip of the bolt protruding inside the yoke 181 to prevent the corrosion-resistant magnet 110 arranged on the opening side of the yoke 181 from being attracted to the back yoke portion 183. This prevents the corrosion-resistant magnet 110 from being pulled into the inside of the yoke 181 and colliding with the back yoke portion 183 when the corrosion-resistant magnet 110 is arranged, causing the corrosion-resistant magnet 110 to crack or chip due to the impact.
[0030] After the corrosion-resistant magnet 110 is attached to the back yoke portion 183, the threaded hole portion 183a is provided with the anticorrosive member 142d shown in FIG. 3. As described above, the threaded hole portion 183a is hardly used except for assembling the magnet during manufacturing or removing the magnet during disassembly. Therefore, after the corrosion-resistant magnet 110 is attached to the yoke 181, the anticorrosive member 142d is arranged in the threaded hole portion 183a so as to come into contact with the corrosion-resistant magnet 110, thereby effectively preventing corrosion of the corrosion-resistant magnet 110. In addition, since the leakage of magnetic flux through the threaded hole portion 183a can be reduced, the utilization efficiency of the magnetic force can be improved and the magnetic force can be prevented from acting on other members. Note that if the corrosion-resistant magnet 110 can be accommodated inside the yoke 181 without applying an impact to the corrosion-resistant magnet 110, the threaded hole portion 183a may be omitted. In that case, the back yoke portion 183 does not have a through hole, and the anticorrosive member 142d filling the through hole is also not necessary.
[0031] In the magnetic adsorption device 180 having the configuration described above, the strength of the adsorption force of the corrosion-resistant magnet 110 having strong magnetic force can be controlled by means of the screw hole portion 181a formed in the screw shaft portion 186 protruding from the back yoke portion 183 and the bolt 188 screwed into the screw hole portion 181a, thereby enabling the magnet to be safely and reliably adsorbed to the object to be adsorbed.
[0032] 1, when the magnetic attraction device 180 is attracted to the attraction target 1000, first, the bolt 188 is screwed into the screw hole 181a of the attraction device main body 180a from the upper end of the screw shaft portion 186, and the tip of the bolt 188 is made to protrude from the tip of the inner yoke portion 185. At this time, the protruding length of the bolt 188 depends on the attraction force of the magnetic attraction device 180, but can be, for example, about 5 mm to 8 mm.
[0033] Then, the magnetic attraction device 180 with the tip of the bolt 188 protruding is brought close to the object to be attracted 1000. Then, the tip of the protruding bolt 188 hits the surface of the object to be attracted 1000, preventing contact between the magnetic attraction device 180 and the object to be attracted 1000, and the magnetic attraction device 180 and the object to be attracted 1000 are held in a state separated from each other via a gap. At this time, the magnetic attraction device 180 is attracted to the object to be attracted 1000 with a weak force or is not attracted at all.
[0034] Thereafter, when the head of bolt 188 is rotated to retract bolt 188, the gap between magnetic attraction device 180 and object to be attracted 1000 gradually decreases, and the force of attraction between them also increases. When bolt 188 is retracted to a position where its tip does not protrude from inner yoke portion 185, the attraction surfaces of outer yoke portion 184 and inner yoke portion 185 come into contact with object to be attracted 1000, as shown in Fig. 1. This causes magnetic attraction device 180 to be attracted to object to be attracted 1000 at its attraction surface.
[0035] On the other hand, when removing the magnetic attraction device 180 from the object to be attracted 1000, in the attracted state shown in Fig. 1, the bolt 188 is rotated about its axis to advance the tip of the bolt 188 toward the object to be attracted 1000. This allows a gap to be formed between the magnetic attraction device 180 and the object to be attracted 1000. The corrosion-resistant magnet 110 used in the magnetic attraction device 180 has an extremely strong attractive force, making it difficult to directly separate them by hand. However, since the attractive force of the magnetic attraction device 180 is inversely proportional to the square of the gap between the yoke 181 and the object to be attracted 1000, simply forming a gap of a few millimeters makes it easy to separate them by hand. As described above, the magnetic attraction device 180 of this embodiment can be attached to and detached from the attraction target 1000, or the position thereof can be adjusted easily and safely.
[0036] [Corrosion-resistant magnets and corrosion-resistant magnetic adsorption structure] Following the above-described overall configuration, the corrosion-resistant magnetic attraction structure 176, which is a particularly characteristic feature of the magnetic attraction device 180 of this embodiment, will be described in detail. In order to explain this feature in detail, the following description will also include the development process from the magnetic attraction device of the conventional structure to the configuration of this embodiment.
[0037] Cathodic protection is used as a corrosion prevention measure for steel structures constructed in seawater. In cathodic protection, an aluminum alloy anode (hereinafter referred to as Al anode), which is a source of a corrosion protection current, is attached to the steel body to be protected from corrosion. Conventionally, underwater welding, in which an arc is directly thrown underwater to weld, has been used as a means of attachment. However, in cases where the body to be protected from corrosion is a steel sheet pile, the inventors have confirmed that underwater welding induces a decrease in the strength of the steel sheet pile, which is a high-tensile steel. The inventors have conducted research to develop an alternative means of attaching an Al anode instead of underwater welding. They have developed a "magnetic adhesion device" that uses the strong magnetic force (adsorption force) of a neodymium magnet to adsorb the Al anode to the steel sheet pile. Furthermore, they have established the "Japan Magnetic Adsorption Construction Method Association" and are working to popularize this technology.
[0038] In the process of developing the magnetic adsorption method, the inventors confirmed the phenomenon of the neodymium magnets in the magnetic adsorption device being corroded and worn out, and investigated the cause. As a result, they confirmed that because the nickel plating layer of the neodymium magnets has a low function as a protective layer, even if the neodymium magnets are electrochemically protected using zinc anodes, even if there is even a slight scratch or defect, corrosion will progress from there. Therefore, with the cooperation of Kagoshima University, they conducted a durability test of neodymium magnets in seawater. As a result, they confirmed that if a defect occurs in the nickel plating layer, the neodymium magnet forms a galvanic cell with the object to be protected from corrosion, and becomes an anode part and is rapidly worn out. In this galvanic cell, the area ratio of the anode part to the cathode part is extremely large, and the potential of the neodymium magnet is -2400mV (SCE), and when the object to be protected reaches the corrosion protection potential, it is around -900mV (SCE), so the potential difference (electromotive force) reaches 1500mV, and since the cathodic polarization accompanying the current hardly progresses, a large corrosion current continues to flow.
[0039] Therefore, it was found that preventing the formation of this large-scale galvanic cell was necessary for the stable long-term use of neodymium magnets in seawater. At the beginning of development, the idea was to address this issue by strengthening the corrosion prevention function of the nickel plating layer, and an electrolytic zinc plating (thickness of about 30 μm) was applied on top of the nickel plating layer to form a nickel-zinc composite plating layer. Then, as a result of conducting a salt spray test on this composite plating layer, it was confirmed that it had a durability of more than 10 times that of the nickel plating layer alone.
[0040] However, when the number of neodymium magnets to be processed with electrolytic zinc plating is small, it is not cost-effective. Therefore, as an alternative, a structure was adopted in which a zinc tape (200 μm thick) was attached to the top of the nickel plating layer to form a sacrificial anode layer. Salt spray tests were conducted on the structure using this zinc tape, and it was confirmed that corrosion resistance was improved by more than seven times compared to electrolytic zinc plating. Therefore, it was confirmed that by strengthening the sacrificial anode function using zinc tape, corrosion caused by galvanic cells could be significantly reduced.
[0041] The application of zinc tape does not require any special techniques or tools, and the zinc anode layer can be formed simply by grinding and degreasing the nickel plating layer applied to the surface of the neodymium magnet, cutting the zinc tape to the specified shape and dimensions, and applying and adhering it to the magnet. This means that the process can be carried out in less time and at a lower cost than electrolytic zinc plating. The thickness of the current zinc tape is 200μm, which is four times the capacity of HDZ55, the thickest standard for hot-dip galvanizing.It also has a blocking function that seals defects (micropores) in the nickel plating layer, eliminating the potential difference between the neodymium magnet and the object to be protected, preventing the formation of a galvanic battery.
[0042] Furthermore, apart from electrochemical means, we thought that it would be possible to prevent the formation of galvanic cells by physically isolating the neodymium magnet from the environment in which it is used. Therefore, we investigated the functions of various insulating paints, lining materials, and fillers currently available on the market. As a result, we found that a solvent-free epoxy resin paint sold under the name "Sigma Guard CSF650" by Amakoat, Inc. in the United States, has extremely excellent insulation properties and durability against seawater. This solvent-free epoxy resin paint can impart extremely high durability when used as a coating material for neodymium magnets when used underwater, and also has the following advantages: (1) No solvents are used. (2) High coverage of corners and edges. (3) High filling ability in damaged areas (open craters, omega craters). (4) The coating has low shrinkage so cracks do not occur.
[0043] This solvent-free epoxy resin paint has been highly praised by the U.S. Navy, which has adopted it, and it is said to have extremely long-term durability of over 100 years. Therefore, we created a sample in which an insulating layer was formed by applying a solvent-free epoxy resin paint onto the nickel plating layer of a neodymium magnet, and a sample in which an insulating layer (lining portion) was formed by filling the area around a neodymium magnet housed in a yoke with solvent-free epoxy resin paint. We then carried out durability tests using salt spray on these samples to confirm their performance. As a result, we confirmed that no changes were observed in the coating or lining portions after about 1000 hours, and that high durability could be achieved over a long period of time. Furthermore, it was confirmed that by appropriately combining electrochemical corrosion prevention measures (strengthening the sacrificial anode function) and physical corrosion prevention measures (forming an insulating coating), the corrosion resistance of permanent magnets can be improved several to several tens of times compared to conventional methods.
[0044] Through the above development process, the corrosion-resistant magnet of the present invention and a magnetic attraction device including the same have been obtained. The following describes embodiments and various modifications of the corrosion-resistant magnet and magnetic attraction device. First, each aspect of the corrosion-resistant magnet 110 will be described with reference to Figs. 3 to 7. Next, each aspect of the magnetic attraction device 180 including the corrosion-resistant magnetic attraction structure 176 will be described with reference to Figs. 8 to 11.
[0045] FIG. 3 is a diagram for explaining the detailed structure of the corrosion-resistant magnetic attraction structure 176 provided in the magnetic attraction device 180, and is an enlarged view of part A in FIG. The corrosion-resistant magnet 110 of the corrosion-resistant magnetic attraction structure 176 includes a neodymium magnet 111 , a zinc coating 112 or first insulating layer 113 , and a zinc anode layer 142 or second insulating layer 143 .
[0046] The neodymium magnet 111 is an example of a permanent magnet, and is not limited to this. In other words, the permanent magnet to be used is not limited to an Nd-Fe-B permanent magnet, but may be an iron-based rare earth permanent magnet represented by RE-Fe-MB (RE is at least one rare earth element selected from the group consisting of Nd, Y, La, Ce, Pr, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, and M is at least one element selected from the group consisting of Co, Ti, Nb, Al, V, Mn, Sn, Ca, Mg, Pb, Sb, Zn, Si, Zr, Cr, Ni, Cu, Ga, Mo, W, and Ta), as well as an Sm-Co magnet, a ferrite magnet, or the like.
[0047] The neodymium magnet 111 is a thin ring-shaped part, and has a pair of upper and lower surfaces, and inner and outer circumferential surfaces connecting the upper and lower surfaces. The upper and lower surfaces of the neodymium magnet 111 are annular flat surfaces that have the same inner and outer diameters and are coaxial with each other. The inner and outer circumferential surfaces of the neodymium magnet 111 are annular, band-shaped arc surfaces that have the same height dimensions and are coaxial with each other. When the neodymium magnet 111 is viewed in a cross section including its central axis, as shown in FIG. 3, the connection points between the upper surface and the inner and outer circumferential surfaces are formed with approximately right-angled corners. Similarly, when the neodymium magnet 111 is viewed in a cross section including its central axis, as shown in FIG. 3, the connection points between the lower surface and the inner and outer circumferential surfaces are also formed with approximately right-angled corners. The upper surface, lower surface, inner peripheral surface, and outer peripheral surface of the neodymium magnet 111 are all covered with nickel coating 111a. All of the above-mentioned corners of the neodymium magnet 111 are also covered with nickel coating 111a. Note that a resin film may be used instead of the nickel coating 111a.
[0048] The entire surface of the neodymium magnet 111, i.e., the entire surface of the nickel coating 111a, is covered with a zinc coating 112 or a first insulating layer 113. Here, the zinc coating 112 includes two types: one consisting of an electrolytic zinc plating layer 112a, and the other consisting of a high-purity zinc tape 112b. The details of the above configuration will be described with reference to Fig. 3 as well as Figs. 4 to 7. Fig. 4 is a partially enlarged cross-sectional view of part B in Fig. 3 turned upside down, showing a configuration coated with an electrolytic zinc plating layer 112a (zinc coating 112). Fig. 5 is a partially enlarged cross-sectional view corresponding to Fig. 4, showing a configuration coated with a high-purity zinc tape 112b (zinc coating 112) instead of the electrolytic zinc plating layer 112a. Fig. 6 is a partially enlarged cross-sectional view corresponding to Fig. 4, showing a configuration coated with a first insulating layer 113 made of a solventless epoxy resin paint instead of the electrolytic zinc plating layer 112a.
[0049] First, in the configuration in which the entire surface of the neodymium magnet 111 is covered with the zinc coating 112, there are two methods: forming an electrolytic zinc plating layer 112a as shown in Figure 4, or covering by attaching a high-purity zinc tape 112b as shown in Figure 5. Either of these two methods can cover and seal the pores h of the nickel coating 111a, but as mentioned above, from the viewpoint of cost and the like, the form of Figure 5 in which the high-purity zinc tape 112b is attached for covering is more preferable.
[0050] On the other hand, when covering the entire surface of the neodymium magnet 111 with the first insulating layer 113 as shown in Fig. 6, the above-mentioned solventless epoxy resin paint is applied to the entire surface of the neodymium magnet 111, i.e., the entire surface of the nickel coating 111a, and then this coating is dried to form the layer. Even with this configuration, the pores h formed in the nickel coating 111a can be covered and sealed with the first insulating layer 113.
[0051] In addition, it is unavoidable that the air is mixed into the solvent-free epoxy resin paint when it is mixed (stirred) before application, and if it is left as it is, this causes air bubbles to be generated in the first insulating layer 113, which is a coating. In particular, when it is used as a lining material (filler) that covers the neodymium magnet 111, as in this embodiment, rather than as a coating, it is required to eliminate the air bubbles in the solvent-free epoxy resin paint. That is, in a lining material that is several to ten times thicker than the coating thickness in the case of normal coating, the influence of air bubbles remaining inside is large, and a difference in insulating function occurs between a healthy part with few air bubbles and an unhealthy part containing many air bubbles due to the difference in coating thickness, and it is likely to cause the coating deterioration to progress. In addition, since the magnetic adsorption device 180 of this embodiment is used in a special way by immersing it in seawater for a long period of time, it is preferable to remove air bubbles in the solvent-free epoxy resin paint by sufficient deaeration. Specifically, the solvent-free epoxy resin paint is applied to the entire surface of the neodymium magnet 111, i.e., the entire surface of the nickel coating 111a, and then the paint is placed in a vacuum tank and dried as is. Then, the air bubbles (air) mixed in the solvent-free epoxy resin paint dissipate outside the film, and the paint can be dried and solidified in a state where the air bubbles have disappeared. This allows the formation of the first insulating layer 113 that is free of air bubbles and provides uniform insulation function for each part, so that the paint exhibits rock-solid insulation against seawater and prevents the progression of corrosion of the neodymium magnet 111.
[0052] On the other hand, when the high purity zinc tape 112b shown in Fig. 5 is attached to and coated on the neodymium magnet 111, the entire surface of the neodymium magnet 111 is coated, for example, by the process shown in Fig. 7. Fig. 7 shows a manufacturing method for the corrosion-resistant magnet 110 according to the embodiment shown in Fig. 5, and shows that the process proceeds in the order of (a), (b), and (c). First, the nickel coating 111a of the neodymium magnet 111 is polished and degreased. 7(a), one strip of high purity zinc tape 112b cut to a length sufficient to cover the entire circumference of the inner circumferential surface of the neodymium magnet 111, and another strip of high purity zinc tape 112b cut to a length sufficient to cover the entire circumference of the outer circumferential surface of the neodymium magnet 111 are prepared. Then, each high purity zinc tape 112b is attached in the circumferential direction so as to cover the entire inner and outer circumferential surfaces of the neodymium magnet 111.
[0053] 7(b), two pieces of high purity zinc tape 112b are prepared, cut into rings wide enough to cover the entire upper and lower surfaces of the neodymium magnet 111. At this time, the ring-shaped high purity zinc tape 112b to be applied later is cut so that its inner circumference is smaller and its outer circumference is larger, so that no gap is created between the high purity zinc tape 112b that was previously applied to the inner and outer circumferential surfaces of the neodymium magnet 111. Then, each high purity zinc tape 112b is applied coaxially to cover the entire upper and lower surfaces of the neodymium magnet 111. Finally, as shown in FIG. 7(c), the inner and outer peripheral parts of the high-purity zinc tape 112b attached to the upper and lower surfaces of the neodymium magnet 111 are folded at right angles to cover the corners connected to the upper and lower surfaces of the neodymium magnet 111. This folding allows the high-purity zinc tapes 112b attached later to be attached so as to overlap the high-purity zinc tapes 112b attached to the inner and outer peripheral surfaces of the neodymium magnet 111. In this way, the entire surface of the neodymium magnet 111, i.e., the entire surface of the nickel coating 111a, is covered with the high-purity zinc tape 112b without any gaps, and the corrosion-resistant magnet 110 can be obtained. As a result, all the pores h can be sealed as described in FIG. 5.
[0054] To use the corrosion-resistant magnet 110 obtained by the manufacturing method exemplified above in the magnetic attraction device 180, the corrosion-resistant magnet 110 is first magnetically attracted to a predetermined coaxial position in the groove 181b of the yoke 181, using the procedure described above. Thereafter, the surface of the corrosion-resistant magnet 110 is covered with a zinc anode layer 142 or a second insulating layer 143, as exemplified in Figures 8 to 11.
[0055] Here, FIG. 8 is a diagram showing the main part of the magnetic adsorption device 180 shown in FIG. 1 turned upside down, and is a vertical cross-sectional view showing the case where the second insulating layer 143 is formed from a solvent-free epoxy resin paint. In this embodiment, a solvent-free epoxy resin paint is filled in the gap between the inner peripheral surface of the corrosion-resistant magnet 110 and the outer peripheral surface of the inner peripheral yoke portion 185, and in the gap between the outer peripheral surface of the corrosion-resistant magnet 110 and the inner peripheral surface of the outer peripheral yoke portion 184, and then solidified to form the second insulating layer 143. Furthermore, the second insulating layer 143 made of solidified solvent-free epoxy resin paint is also formed on the surface of the corrosion-resistant magnet 110 facing the opening of the yoke 181 (the surface of the corrosion-resistant magnet 110 on the upper side of the paper in FIG. 8). With the second insulating layer 143 formed on these three surfaces, it is possible to further improve the corrosion resistance by overlapping and covering the entire surface of the corrosion-resistant magnet 110 to which corrosion resistance has been imparted with the second insulating layer 143. Moreover, the second insulating layer 143 formed on the surface facing the opening of the yoke 181 is disposed at the back side of the groove portion 181b, and is therefore disposed at a position separated from the attraction target 1000 with a gap therebetween when the magnetic attraction device 180 is attracted to the attraction target 1000. Therefore, the second insulating layer 143 is disposed in such a manner that it is not damaged by direct contact with the attraction target 1000.
[0056] However, as described above, the solvent-free epoxy resin paint inevitably mixes with air during mixing (stirring) before application, and if left as is, this causes air bubbles to form in the second insulating layer 143. In particular, when the paint is used as a lining material (filler) rather than a coating, as in this embodiment, it is required to eliminate the air bubbles in the second insulating layer 143. That is, in a lining material that is several to ten times thicker than the coating thickness in the case of normal coating, the influence of air bubbles remaining inside is large, and a difference in insulating function occurs between healthy parts with few air bubbles and unhealthy parts with many air bubbles due to the difference in coating thickness, and it is likely to cause the coating deterioration to progress. In addition, since the magnetic adsorption device 180 of this embodiment is used in a special way by immersing it in seawater for a long period of time, it is preferable to remove air bubbles in the second insulating layer 143 by sufficient deaeration. Specifically, the corrosion-resistant magnet 110 is placed inside the yoke 181, which is then filled with and covered with a solvent-free epoxy resin paint, which is then placed inside a vacuum tank and left to dry. This causes the air bubbles (air) mixed in the solvent-free epoxy resin paint to dissipate outside the film, allowing the paint to dry and solidify in a state where the air bubbles have disappeared. This allows the second insulating layer 143 to be formed without any air bubbles inside, allowing the insulating function of each part to be uniform, providing rock-solid insulation against seawater and preventing the progression of corrosion of the neodymium magnet 111.
[0057] Fig. 9 corresponds to Fig. 8 and is a vertical cross-sectional view showing a case where a flexible zinc anode is filled around the corrosion-resistant magnet 110 to form a zinc anode layer (sacrificial anode layer) 142. The flexible zinc anode is made by mixing zinc powder or zinc alloy powder with a resin material or the like to form a paste.
[0058] In this embodiment, a flexible zinc anode is filled in the gap between the inner peripheral surface of the corrosion-resistant magnet 110 and the outer peripheral surface of the inner peripheral yoke portion 185, and in the gap between the outer peripheral surface of the corrosion-resistant magnet 110 and the inner peripheral surface of the outer peripheral yoke portion 184, and is solidified to form a zinc anode layer 142. Furthermore, a zinc anode layer 142 formed by solidifying the flexible zinc anode is also formed on the surface of the corrosion-resistant magnet 110 facing the opening of the yoke 181 (the surface of the corrosion-resistant magnet 110 on the upper side of the paper in FIG. 9). The zinc anode layers 142 formed on these three surfaces form the corrosion protection members 142a, 142b, and 142c. In this way, by overlapping and covering the entire surface of the corrosion-resistant magnet 110 to which corrosion resistance has been imparted with zinc anode layer 142, it is possible to further improve the corrosion resistance. Moreover, the zinc anode layer 142 formed on the surface facing the opening of the yoke 181 is disposed at the back side of the groove portion 181b, so that when the magnetic attraction device 180 is attracted to the attraction target 1000, the zinc anode layer 142 is disposed at a position separated from the attraction target 1000 with a gap therebetween. Therefore, the zinc anode layer 142 is disposed in such a manner that it is not damaged by direct contact with the attraction target 1000.
[0059] The zinc anode layer 142 may be a paste (putty) having viscosity at least when applied, and may be solidified by a heating treatment or a drying treatment after application. Furthermore, the zinc anode layer 142 may not have electrical conductivity when applied, and may become electrically conductive by a heating treatment or a drying treatment. As the metal powder contained in this zinc anode layer 142, zinc is most suitable in consideration of the anode potential, anode efficiency, amount of electrolytic product generated, and ease of handling.
[0060] The zinc anode layer 142 is preferably formed to a thickness of 50 μm or more, and more preferably to a thickness of 500 μm or more. Furthermore, if the thickness is 1 mm or more, it becomes a corrosion-resistant member that can obtain a corrosion-resistant effect for an extremely long period of time. With such a configuration, it is possible to configure the corrosion-resistant magnetic attraction structure 176 with a sufficient amount of corrosion-resistant member, so that it will not corrode even if used in water or seawater for a long period of time and can maintain its attraction force.
[0061] Fig. 10 is a diagram corresponding to a modified example of Fig. 8, and is a vertical cross-sectional view showing a case where a second insulating layer 143 is formed by applying a solvent-free epoxy resin paint to the periphery of the corrosion-resistant magnet 110 when covered with a high-purity zinc tape 112b. That is, in the configuration described in Fig. 8, only the configuration of the corrosion-resistant magnet 110 is different, and the rest is the same as the configuration in Fig. 8. Figure 11 is a diagram corresponding to a modification of Figure 9, and is a vertical cross-sectional view showing a case where a corrosion-resistant magnet 110 covered with high-purity zinc tape 112b is surrounded by a flexible zinc anode to form a zinc anode layer 142. That is, in the configuration described in Figure 9, only the configuration of the corrosion-resistant magnet 110 is different, and the rest is the same as the configuration in Figure 9.
[0062] The main features of the corrosion-resistant magnet 110 and the magnetic attraction device 180 described above will be summarized below. (1) As shown in FIG. 3, a corrosion-resistant magnet 110 according to one embodiment of the present invention is A neodymium magnet (permanent magnet) 111 covered with a nickel coating 111a; A zinc coating 112 formed on the nickel coating 111a; has. (2) As shown in FIG. 4, in the corrosion-resistant magnet 110 described in (1) above, the zinc coating 112 may be an electrolytic zinc plating layer (zinc plating) 112a. (3) As shown in FIG. 5, in the corrosion-resistant magnet 110 described in (1) above, the zinc coating 112 may be a high-purity zinc tape 112b.
[0063] (4) As shown in FIG. 6, a corrosion-resistant magnet 110 according to another embodiment of the present invention is A neodymium magnet (permanent magnet) 111 covered with a nickel coating 111a; a first insulating layer 113 made of epoxy resin formed on the nickel coating 111a; has.
[0064] (5) As shown in FIG. 1, a magnetic adsorption device 180 according to an embodiment of the present invention is A corrosion-resistant magnet 110 according to any one of the above (1) to (4), A yoke 181 that holds the corrosion-resistant magnet 110; Equipped with.
[0065] (6) As shown in FIG. 3, the magnetic adsorption device 180 described in (5) above is The corrosion resistant magnet 110 may further include a zinc anode layer 142 coating the surface thereof.
[0066] (7) As shown in FIG. 1, the magnetic adsorption device 180 described in (6) above may have the following configuration: The corrosion-resistant magnet 110 is ring-shaped, York 181, A back yoke portion 183 that is attracted to the corrosion-resistant magnet 110; An outer yoke portion 184 that is integrally formed with the back yoke portion 183 and surrounds the corrosion-resistant magnet 110; an inner yoke portion 185 disposed on the inner periphery side of the corrosion-resistant magnet 110 and integrally formed with the back yoke portion 183; The zinc anode layer 142 is Between the outer peripheral surface of the corrosion-resistant magnet 110 and the inner peripheral surface of the outer peripheral yoke portion 184, Between the inner peripheral surface of the corrosion-resistant magnet 110 and the outer peripheral surface of the inner peripheral yoke portion 185, a surface of the corrosion-resistant magnet 110 opposite to the surface that is attracted to the back yoke portion 183; is formed.
[0067] (8) As shown in FIG. 8, in the magnetic adsorption device 180 described in (5) above, A second insulating layer 143 made of epoxy resin formed on the surface of the corrosion-resistant magnet 110. The device may further include:
[0068] (9) As shown in FIG. 8, the magnetic adsorption device 180 described in (8) above may have the following configuration: The corrosion-resistant magnet 110 is ring-shaped, York 181, A back yoke portion 183 that is attracted to the corrosion-resistant magnet 110; An outer yoke portion 184 that is integrally formed with the back yoke portion 183 and surrounds the corrosion-resistant magnet 110; an inner yoke portion 185 disposed on the inner periphery side of the corrosion-resistant magnet 110 and integrally formed with the back yoke portion 183; The second insulating layer 143 is Between the outer peripheral surface of the corrosion-resistant magnet 110 and the inner peripheral surface of the outer peripheral yoke portion 184, Between the inner peripheral surface of the corrosion-resistant magnet 110 and the outer peripheral surface of the inner peripheral yoke portion 185, a surface of the corrosion-resistant magnet 110 opposite to the surface that is attracted to the back yoke portion 183; is formed.
[0069] According to the corrosion-resistant magnet 110 described in (1) to (4) above, the pores h on the surface of the nickel coating 111a are covered by the zinc coating 112 or the first insulating layer 113. Therefore, even if this corrosion-resistant magnet 110 is used for a long period of time in a high humidity environment or underwater (including seawater), moisture or water will not reach the neodymium magnet 111 through the pores in the nickel coating 111a, so dissolution of the neodymium magnet 111 can be prevented. Therefore, this corrosion-resistant magnet 110 has high corrosion resistance that can withstand long-term use in a high humidity environment or underwater. According to the magnetic attraction device 180 described in (5) to (9) above, since the corrosion-resistant magnet 110 is provided, it is possible to continue to exhibit high magnetic attraction for the long term.
[0070] In the above-described embodiments, the shape of the chucking surface of the outer circumferential yoke portion 184 with respect to the chucking target object 1000 is a ring shape when viewed from the opposite side. However, the chucking surface is not limited to a circular shape, and other shapes such as a rectangular shape or an elliptical shape may be adopted. For example, when a rectangular frame shape is adopted as the shape of the chucking surface, this rectangular frame shape may be a square or a rectangle. Moreover, the magnetic adsorption device 180 of each embodiment described above can be used for various purposes, whether on land or in seawater. For example, in civil engineering and construction applications, it can be suitably used for assembling steel structures such as iron poles and iron plates, and attaching accessories to steel structures. In this application, assembly and attachment have traditionally been performed using processing means such as welding, riveting, and bolt fastening, but by adopting the magnetic adsorption device of the present invention, these can be strongly adsorbed to obtain strength equivalent to that obtained by the above processing means, thereby obtaining effects such as shortening the construction period and improving work efficiency. Furthermore, since it can be removed as necessary, if it is used for setting up a work scaffold, removal work can also be performed quickly. [Explanation of symbols]
[0071] 110...Corrosion-resistant magnet 111...Neodymium magnet (permanent magnet) 111a...Nickel coating 112...Zinc coating 112b…High-purity zinc tape (zinc tape) 113...First insulating layer 142...Zinc anode layer 143...Second insulating layer 180...Magnetic adsorption device 181…York 183…Back yoke 184…Outer yoke part 185…Inner yoke part
Claims
1. A permanent magnet coated with nickel; a zinc coating formed on the nickel coating; A corrosion-resistant magnet comprising:
2. The zinc coating is zinc plating.
2. The corrosion-resistant magnet according to claim 1 .
3. The zinc coating is a zinc tape.
2. The corrosion-resistant magnet according to claim 1 .
4. A permanent magnet coated with nickel; a first insulating layer made of an epoxy resin formed on the nickel coating; A corrosion-resistant magnet comprising:
5. A corrosion-resistant magnet according to any one of claims 1 to 4; a yoke that holds the corrosion-resistant magnet; Equipped A magnetic adsorption device characterized by:
6. A zinc anode layer coating the corrosion resistant magnet The magnetic adsorption device according to claim 5 , further comprising:
7. The corrosion-resistant magnet is ring-shaped; The yoke is A back yoke portion that is attracted to the corrosion-resistant magnet; an outer yoke portion formed integrally with the back yoke portion and surrounding the corrosion-resistant magnet; an inner yoke portion disposed on the inner periphery side of the corrosion-resistant magnet and integrally formed with the back yoke portion; The zinc anode layer is Between an outer peripheral surface of the corrosion-resistant magnet and an inner peripheral surface of the outer peripheral yoke portion, Between an inner peripheral surface of the corrosion-resistant magnet and an outer peripheral surface of the inner peripheral yoke portion, a surface of the corrosion-resistant magnet opposite to an attracting surface with the back yoke portion; It is formed in 7. The magnetic adsorption device according to claim 6.
8. A second insulating layer made of epoxy resin formed on the surface of the corrosion-resistant magnet. The magnetic adsorption device according to claim 5 , further comprising:
9. The corrosion-resistant magnet is ring-shaped; The yoke is A back yoke portion that is attracted to the corrosion-resistant magnet; an outer yoke portion formed integrally with the back yoke portion and surrounding the corrosion-resistant magnet; an inner yoke portion disposed on the inner periphery side of the corrosion-resistant magnet and integrally formed with the back yoke portion; The second insulating layer is Between an outer peripheral surface of the corrosion-resistant magnet and an inner peripheral surface of the outer peripheral yoke portion, Between an inner peripheral surface of the corrosion-resistant magnet and an outer peripheral surface of the inner peripheral yoke portion, a surface of the corrosion-resistant magnet opposite to an attracting surface with the back yoke portion; It is formed in 9. The magnetic adsorption device according to claim 8.
Citation Information
Patent Citations
Permanent magnet and manufacturing method therefor
JP2004039917A
Corrosion prevention structure
JP2008144257A
Corrosion prevention method for sintered metal, corrosion resistant magnet and magnetic attracting device
JP2008274358A
Corrosion preventing structure and corrosion preventing method for marine steel structure steel member
JP2011032744A
Corrosion preventive method for permanent magnet
JP2013047387A